Comparison of the Copan WASPLab incorporating the BioRad expert system against the SIRscan 2000 automatic for routine antimicrobial disc diffusion susceptibility testing. (May 2020) - Cherkaoui, A.; Renzi, G.; Fischer, A.; Azam, N.; Schorderet, D.; Vuilleumier, N.; Schrenzel, J.
Abstract: Objectives: This study investigated the agreement at the categorical level between the Copan WASPLab incorporating the BioRad expert system against the SIRscan 2000 automatic for antimicrobial disc diffusion susceptibility testing. Methods: The 338 clinical strains (67 Pseudomonas aeruginosa, 19 methicillin-resistant Staphylococcus aureus, 75 methicillin-sensitive S. aureus and 177 Enterobacterales isolates) analysed in this study were non-duplicate isolates obtained from consecutive clinical samples referred to the clinical bacteriology laboratory at Geneva University Hospitals between June and August 2019. For the WASPLab the inoculum suspension was prepared in strict accordance with the manufacturer's instruction (Copan WASP srl, Brescia, Italy) by adding 2 mL of the 0.5 McFarland primary suspension used for the SIRscan analysis into a sterile tube filled with 4 mL of sterile saline (1:3 dilution). The inoculum (2 × 30 μL loop/spreader) was spread over the entire surface of Mueller–Hinton agar plates according to the AST streaking pattern defined by Copan. The antibiotic discs were dispensed by the WASP and inoculated media were loaded on conveyors for transfer to the automatic incubators. The plates were incubated for 16 h, and several digital images were acquired. Inhibition zone diameters were automatically read by the WASPLab and were adjusted manually whenever necessary. For the SIRscan 2000 automatic, the antimicrobial disc diffusion susceptibility testing was performed according to the EUCAST guidelines. The gradient strip method was used to resolve discrepancies. Results: The overall categorical agreement between the compared methods reached 99.1% (797/804; 95% CI 98.2%–99.6%), 99.5% (1029/1034; 95% CI 98.9%–99.8%), and 98.8% (2798/2832; 95% CI 98.3%–99.1%) for P. aeruginosa, S. aureus and the Enterobacterales, respectively. Conclusions: WASPLab incorporating the BioRad expert system provides a fully automated solution for antimicrobial disc diffusion susceptibility testing with equal or better accuracy than other available phenotypic methods.